The contribution of OCTN1/2 variants within the IBD5 locus to disease susceptibility and severity in Crohn’s disease - Noble, C; Nimmo, E; Drummond, H; Ho, G; Tenesa, A; Smith, L; Anderson, N; Arnott, I; Satsangi, J (Elsevier, 2005)
Background & Aims: Recent data suggest that polymorphisms in the organic cation transporter (OCTN) genes OCTN1 (SLC22A4) and OCTN2 (SLC22A5) represent disease-causing mutations within the IBD5 locus (chromosome 5q31). We investigated associations with disease susceptibility, phenotype, and evidence for epistasis with CARD15 in 679 patients with Crohn’s disease (CD) or ulcerative colitis (UC). Methods: A total of 374 patients with CD, 305 patients with UC, and 294 healthy controls (HCs) were studied. Genotyping for single nucleotide polymorphisms IGR2096, IGR2198, and IGR2230, OCTN1 variant (SLC22A4 1672C→T), and OCTN2 variant (SLC22A5 −207G→C) was performed using the TaqMan system. Results: The IBD5 OCTN1 and OCTN2 polymorphisms were in strong linkage disequilibrium (D′, >0.959). IGR2198 variant allele frequency (49.1% vs 40.8%; P = .0046) and homozygosity (21% vs 14.8%; P = .044) were associated with CD versus HCs. Variant allelic frequency of OCTN1 (53.6% vs 43%; P = .0008) and OCTN2 (56.1% vs 48.4%; P = .0092) polymorphisms and homozygosity for the OCTN1/2-TC haplotype (28.4% vs 16%; P = .0042) were associated with CD versus HCs. IGR2198 homozygosity and TC homozygosity were associated with stricturing/penetrating disease at follow-up (P = .011 and P = .011, respectively) and disease progression (P = .038 and P = .049, respectively) on univariate analysis and with need for surgery on multivariate analysis (P = .016 and P = .004, respectively). In the absence of the IBD5 risk haplotype, no association of OCTN1/2 variants with CD was detected. No associations were seen with UC. Conclusions: The IBD5 locus influences susceptibility, progression, and need for surgery in CD. However, the contribution of OCTN1/2 variants is not independent of the IBD5 haplotype; a causative role for these genes remains plausible but is not yet proven. Further genetic, functional, and expression data are now required.